Adobe After Effects CS5 : visual effects and compositing : studio techniques - Christiansen, Mark (Visual effects specialist) (Adobe Press, 2011)
This is the only book on the market to focus exclusively on the creation of visual effects for After Effects users, and is a one-stop resource for anyone who wants in-depth explanations that demystify the realm of visual effects and how they were created, thanks to veteran author Mark Christiansen39;s friendly and accessible style. A thoroughly packed, informative read, this masterful guide focuses on explaining the essential concepts, features, and techniques that are key to creating seamless movie-quality visual effects. Users who are comfortable with After Effects will find a helpful review of the fundamentals - managing footage, viewing and editing layers, animating type, and more - so they can learn how to work smarter and more efficiently. Readers of all levels will learn core techniques for effects compositing including color matching, keying, rotoscoping, motion tracking, emulating the camera, and concluding with using expressions in After Effects, written by contributor and expert Dan Ebberts. An incredibly useful appendix on scripting in After Effects is included as well, written by Adobe engineer Jeff Almasol. The final section of the book delves into creative explorations, demonstrating professional effects that are commonly seen in films and games which readers can re-create. Readers will also find comprehensive coverage of all that39;s new and makes this version of Adobe39;s effects programa must-have update, including the revolutionary new Roto Brush, all new effects such as the New Refine Matte effect, new support for Color Look-Up Tables, workflows that take advantage of the all-new 64-bit support, inclusion of third-party tools for additional creativity, and much more.